2013
DOI: 10.1016/j.jconrel.2013.06.038
|View full text |Cite
|
Sign up to set email alerts
|

High concentrations of drug in target tissues following local controlled release are utilized for both drug distribution and biologic effect: An example with epicardial inotropic drug delivery

Abstract: Local drug delivery preferentially loads target tissues with a concentration gradient from the surface or point of release that tapers down to more distant sites. Drug that diffuses down this gradient must be in unbound form, but such drug can only elicit a biologic effect through receptor interactions. Drug excess loads tissues, increasing gradients and driving penetration, but with limited added biological response. We examined the hypothesis that local application reduces dramatically systemic circulating d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…PV conductance catheters can be used as a continuous real-time monitor of cardiovascular function but such use is more complicated and somewhat more limited than at specific points in time. Continuous experiments are often pharmacologic interventions that produce acute haemodynamic changes, on the order of minutes to hours, and can be performed while the PV catheter remains in situ for the duration of the treatment [10, 11]. We have found that such real-time monitoring during pharmacologic treatment can only be performed with frequent manipulation to optimise position, which can lead to disruptions in continuous signals.…”
Section: Introductionmentioning
confidence: 99%
“…PV conductance catheters can be used as a continuous real-time monitor of cardiovascular function but such use is more complicated and somewhat more limited than at specific points in time. Continuous experiments are often pharmacologic interventions that produce acute haemodynamic changes, on the order of minutes to hours, and can be performed while the PV catheter remains in situ for the duration of the treatment [10, 11]. We have found that such real-time monitoring during pharmacologic treatment can only be performed with frequent manipulation to optimise position, which can lead to disruptions in continuous signals.…”
Section: Introductionmentioning
confidence: 99%
“…An alginate polymeric local drug releasing system, designed to precisely administer animal-weight based amounts of epinephrine to the epicardium, was fabricated from calcium-cross-linked alginate hydrogels [29, 30]. Briefly, 0.65 ml of 2% alginate (#71238; Sigma-Aldrich) slurry in double distilled water (ddH20) was pipetted onto the upper side of the permeable membrane of a transwell support (#3472, 24 mm, polyester, 3 μm pore size; Corning).…”
Section: Methodsmentioning
confidence: 99%
“…Each release rate was then linearly correlated to the applied concentration. This relationship, specific to these disks at the fixed volume and interval of applied drug solution, allows the release rate to be prescribed solely through adjustments in applied concentration [29, 30]. This novel method of controlling epicardial drug release allows for precise animal weight-based dosing without any chemical modifications to the polymer platform.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatives routes of milrinone therapy do not currently exist, although novel inotrope delivery by a nebulized inhaled route (NCT 02077010 and 01571037) has been studied in humans and topical milrinone administration has been reported in nonhuman models. 34 Oral milrinone and its derivatives have been assessed in several historical clinical trials but demonstrated detrimental effects or lack of efficacy. 35,36 Study Limitations…”
Section: Future Considerationsmentioning
confidence: 99%